Artistic Mimesis or Mimetic “Play” in Relation to Sports Theory - Daniel Shorkend (Budapest International Research and Critics University, 2019)
I shall briefly discuss mimesis in sport in order to compare the use of the term in art with its use in the context of sport. I do this through the application of the “four orders of mimesis” within the general categories of the premodern, the modern and the postmodern as applied to sport. This is achieved through a rehearsal of arguments gleaned from theorists of sport which converge as aspects of mimesis. The reason for doing so is that if a similar mimetic quality can be found in both the disciplines of art and sport,, then it appears that there is a relationship between them and, in agreement with Huizinga (1949), I concede that this common “element” is “play” and more specifically that this commonality can be described as mimetic “play”. However, we first need to discern a common mimetic quality historically associated with sport. Once that is achieved, an analysis of “play” follows and I close with two deductions that the art-sport dialectic, via the lens of “play” suggests conceptually.